Monitoring heavy metal bioaccumulation in rivers using damselflies (Insecta: Odonata , Zygoptera) as biological indicator - Ahmad Hadri Jumaat,; Suhaila Ab Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Contamination by pollutants in freshwater ecosystem has been identified extensively in river, sediments, and freshwater biota. Pollutants may have incorporated into the sediments and accumulated in tissue of aquatic organisms which persist as difficult to degrade matter in upper trophic level. Therefore, few selected heavy metals were measured from the river sediment and tissue of damselflies larvae collected from the selected rivers using inductively coupled plasma optical emission spectrometry (ICP-OES). The results showed metals in damselflies tissue were higher than in the sediments. Mn and Zn were found in greatest concentrations both in sediment and damselflies ’s tissue. Biotasediment accumulation factors (BSAF) were computed based on these data, and it was discovered that all values of BSAF for Cd, Cu, Mn, and Zn were typically high (BSAF >1). In conclusion, the rivers contamination induced accumulation of heavy metal in the river sediments and damselflies larvae (Pseudagrion microcephalum, Pruinosum fraseri, and Copera marginipes). The highest concentration value was calculated as 29.23 for Cd in the C. marginipes. The high concentrations of this element in the insect body tissue has shown a trace of bioaccumulation and may pose biomagnification to organisms in the upper trophic level. The results of this study indicated that damselfly is reliable to become a bioindicator for heavy metals particularly pollution in the river.